Infiltrative resins as a treatment for dental fluorosis. A literature review - Villegas Salhuana, Juleyska (2022)
In recent years, a new standard of resins called infiltrative resins has been generated, which were developed with the aim of contributing to non-invasive treatments, being used as a treatment for the diagnosis of non-cavitated carious lesions; although, currently its use has expanded to treat other types of lesions that affect the enamel such as dental fluorosis. For this review article, original articles, in vitro and in vivo research, case reports, systematic and literature reviews were selected; carrying out the search in 6 databases: PubMed, Google Scholar, ScienceDirect, Wiley, EBSCO and Springer, from which information was obtained about the efficacy, benefits, clinical applications and application technique of the infiltrative resins.